Innovative Learning Strategies Towards Improving Students' Arabic Speaking Skills: A Systematic Literature Review - Qurratul Aini; Wahyu Suci Anggrayani; Fathul Maujud (Sustainable, 2025)
This study presents a Systematic Literature Review (SLR) on innovative instructional strategies designed to improve students’ Arabic speaking skills (mahārah kalām) across varied educational settings. The review applied the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) procedure, including identification, screening, eligibility, and inclusion stages. Literature was retrieved from Google Scholar using keywords related to Arabic pedagogy and innovative learning. A total of 250 articles were initially found; 175 were excluded because they did not focus on speaking skills or did not meet methodological and thematic criteria. The remaining 75 studies published between 2015 and 2025 were analyzed qualitatively. The synthesis shows that Project-Based Learning (PBL), Total Physical Response (TPR), muhadasah practice, eclectic methods, and technology-enhanced media consistently contribute to improvements in fluency, pronunciation, vocabulary mastery, and communicative confidence. These strategies demonstrate alignment with communicative, behaviorist, cognitive, and constructivist learning paradigms through authentic communication, reinforcement, cognitive engagement, and experiential learning. Despite these promising results, research gaps remain, particularly the lack of comparative studies and limited exploration in higher education and nonformal learning contexts. The study underscores the need for integrative, technology-driven instructional models to strengthen Arabic-speaking pedagogy responsive to twenty-first-century learning demands.